Basic Literacy Program Based on Experiential Learning at Fathia Islamic Elementary School, Sukabumi City - Yuniawati, Nia; Lyesmaya, Dyah; Amalia, Arsyi Rizqia (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Basic literacy skills become a strong foundation for mastering knowledge in the next grade. Basic literacy skills are part of language skills learning which is the basis for improving cultural competency in reading and writing. Experiential learning is a learning method through the formation of students' experiences. The significance of basic literacy being so important has apparently not been able to provide awareness for various parties involved in the world of education to immediately rush to improve mastery of basic literacy. This encouraged researchers to look at and analyze literacy activities in the elementary school environment, using qualitative research methods such as case studies and the main focus of this research was the experiential learning-based basic literacy program carried out at Fathia Islamic Elementary School, Sukabumi City, focused on the lower classes. The data sources for this research are interviews, observation and documentation. Based on the research results, it is divided into planning consisting of adequate human resources and training, supporting facility resources, allocated funding resources. The implementation part consists of habits that prioritize a combination of general and religious learning such as 15-minute reading and murojaah. The development section for each teacher creates media, modules and teaching materials based on creativity related to literacy. The obstacle factors are that not all stakeholders are able to collaborate well in the literacy movement and funding is not yet optimal.